Investigation of Memory Enhancing Activity of Madhuca longifolia Leaf Extract against Colchicine: An Experimental Study and Biochemical Alterations in Mice - Khare, Pragati; Kishore, Kamal; Sharma, Dinesh Kumar (Indian Journal of Pharmaceutical Education and Research, 2022)
Objectives: The present study aimed at investigating the protective role of Madhuca longifolia ethanolic leaf extract flavonoid fraction against colchicine induced cognitive dysfunction and oxidative damage in swiss albino mice and to estimate the biochemical alterations in mice brain. HPTLC, total flavonoid and total phenols were also estimated in the study. Materials and Methods: The analysis was conducted on a colchicineinduced model for 28 days. Morris water maze and passive avoidance paradigm were utilized for behavioral experiments, while biochemical parameters such as nitric oxide and glutathione were estimated. Swiss albino mice (48) were apportioned into eight sets, each consisting of six mice. 1 percent w/v carboxy methyl cellulose was apportioned to the first Group. The second group got 200 milligrammes/kg of Piracetam i.p. Group III received 1 mg / kg i.c.v. colchicine. The fourth and fifth set of groups was given 100 and 200 mg / kg ethanolic Madhuca longifolia leaf extract. Group VI has been given Piracetam (200 mg / kg, i.p.) for 28 days and Colchicine 1 mg / kg, i.p., at 60 min after 28th day piracetam injection. Group VII and VIII obtained oral extracts of Madhuca longifolia leaf 100 and 200 mg/kg for 28 days and injected colchicine (1 mg / kg) i.c.v for 90 mins after extract administration on the 28th day. ANOVA (one-way) was utilized and then followed by the test of Dunnett’s and finally outcomes analyzed. Results: Madhuca longifolia leaf extract indicated morris water maze and had a substantial reduction in transfer latency. The transfer latency of the passive avoidance model showed a substantial increase. The Madhuca longifolia leaf extract presented a substantial increase (P<0.001) in GSH intensities and a major decline (P<0.001) in total protein and NO. Conclusion: Madhuca longifolia has neuroprotective effect against memory damage caused by colchicine
Keywords: Madhuca longifolia; Neuroprotective; Alzheimer’s disease; Colchicine; HPTLC; Cognition